Biblical Anthropology and the Cosmic Conflict: An overview with directed emphasis on the Writings of Ellen White - Tutsch, Cindy (Revista Estrategias para el Cumplimiento de la Misión, 2015)
This article deals about anthropology, the human nature, in relationship with the Cosmic Conflict as is presented by Ellen White. The purpose is to have a better understanding how this conflict, which began in heaven with Satan and established on Earth according to Genesis 3, influence our nature today. In relationship with the Great Conflict between Christ and Satan, it is very important focus not only in the consequences of sin for us today, but to see the solution for this Conflict, as the Bible and Ellen White teach, which will end with the glorious coming of Jesus soon, following what Ellen White wrote about this issue.